2019
DOI: 10.1021/jacs.8b12927
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electric Fields Experienced by Urea Guest Molecules in the 18-Crown-6/Urea (1:5) Host–Guest Complex: An Experimental Reference Point for Electric-Field-Assisted Catalysis

Abstract: High resolution synchrotron and neutron single crystal diffraction data of 18-crown-6:(pentakis)urea measured at 30 K are combined, with the aim to better appreciate the electrostatics associated with intermolecular interactions in condensed matter. With two 18-crown-6 molecules and five different urea molecules in the crystal, this represents the most ambitious combined X-ray/synchrotron and neutron experimental charge density analysis to date on a co-crystal or host-guest system incorporating such a large nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 121 publications
3
36
0
Order By: Relevance
“…In 2014, Boxer and coworkers offered experimental support for this hypothesis by demonstrating a link between charge anisotropy in enzymes and chemical catalysis through the exploitation of the vibrational Stark effect. These findings have recently been corroborated in a more direct manner by Spackman and coworkers . In their study, a combined X‐ray/synchrotron and neutron experimental charge density analysis was performed on a cocrystal of urea and 18‐crown‐6 molecules; a model mimicking the substrate selectivity of enzymes.…”
Section: Experimental and Biological Manifestations Of External Electmentioning
confidence: 61%
“…In 2014, Boxer and coworkers offered experimental support for this hypothesis by demonstrating a link between charge anisotropy in enzymes and chemical catalysis through the exploitation of the vibrational Stark effect. These findings have recently been corroborated in a more direct manner by Spackman and coworkers . In their study, a combined X‐ray/synchrotron and neutron experimental charge density analysis was performed on a cocrystal of urea and 18‐crown‐6 molecules; a model mimicking the substrate selectivity of enzymes.…”
Section: Experimental and Biological Manifestations Of External Electmentioning
confidence: 61%
“…Very recently, also the electric field in a complex co‐crystal of 18‐crown‐6/urea was investigated using the experimental ED, and it was shown that all urea molecules aligned with the electric field exerted by the rest of the structure, and that a significant dipole enhancement of the guest molecules occur . The EF inside the cavities were on the order of 10–19 GV m −1 , similar to those established at active sites in proteins .…”
Section: Materials Classesmentioning
confidence: 78%
“…Very recently,a lso the electric field in ac omplex co-crystal of 18-crown-6/urea was investigated using the experimental ED, and it wasshown that all urea molecules aligned with the electric field exerted by the rest of the structure, and that as ignificant dipole enhancement of the guest molecules occur. [96] The EF inside the cavities were on the order of 10-19 GV m À1 ,s imilar to those established at active sites in proteins. [97] These EFs are much larger than the macroscopic fields that can be applied to ac rystal in the laboratory,b efore dielectric breakdown, [98] making inclusion compounds very interesting model systemsf or the response to high local EFs inside proteins and materials.…”
Section: Gas Storage and Host-guest Complexesmentioning
confidence: 99%
“…= 51.4 V/Å). The magnitude of this LEF is at the lower end of the range of LEFs usually observed for proteins . Nevertheless, the LEF of the protein matrix in P450 OleT JE has the right orientation to facilitate the studied H‐abstraction reaction, that is, lower the reaction barrier (cf.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Boxer and coworkers offered experimental support for this hypothesis by demonstrating a link between charge anisotropy in enzymes and chemical catalysis through the exploitation of the vibrational Stark effect . Subsequently, these findings were corroborated in a direct manner by Spackman and coworkers . Together, these two landmark experimental studies constitute compelling experimental evidence that electrostatics is indeed an important factor in biochemical catalysis that cannot be neglected.…”
Section: Introductionmentioning
confidence: 95%